Development of Sigil-Assisted Interactive E-Modules on Basic PBO Concepts in Python - Bilqis Faridah; Muchamad Arif (EDUTIC, 2026)
The learning problem identified by researchers in the 11th grade RPL class at SMK Semen Gresik was the lack of textbooks or handbooks for students, making it difficult for both teachers and students to learn Object-Oriented Programming (OOP), particularly the basic concepts of OOP. The purpose of this study was to determine whether the Sigil-assisted Interactive E-Module was suitable for 11th grade students and whether it was effective. The development used ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results were based on validation data from material experts (85%), media experts (92%), and small group trials (81%) and large group trials (82%). The N-Gain Test value of the study was 0.7, indicating an increase in learning outcomes. The assessment results indicated that the developed E-Module was highly feasible and effective for use during learning